Life-threatening ventricular tachyarrhythmias in the cardiology department: Implications for appropriate prescription of telemetry monitoring. (April 2016) - Zorzi, Alessandro; Peruzza, Francesco; Stella, Federica; Del Monte, Alvise; Migliore, Federico; Gasparetto, Nicola; Badano, Luigi; Iliceto, Sabino; Corrado, Domenico
Abstract: Background: in-hospital life-threatening ventricular arrhythmias (LT-VA) may complicate the course of cardiovascular patients. We aimed to assess the incidence, circumstances, determinants, and outcome of in-hospital LT-VA in order to help clinicians in prescribing appropriate levels of monitoring. Methods: the study population consisted of all 10, 741 consecutive patients (65 ± 15 years, 67.7% males) admitted to a cardiology department in 2009–2014. Terminally ill patients and those with primary arrhythmia diagnosis were excluded. The composite end-point included sudden arrhythmic death, ventricular fibrillation, unstable ventricular tachycardia and appropriate ICD shock unrelated to invasive interventions. Results: the incidence of LT-VA was 0.6%, with no differences regarding age, gender and primary diagnosis of coronary artery disease between patients with and without LT-VA. The incidence of LT-VA was significantly higher (1.2% versus 0.1%, p  < 0.001) among urgent compared with elective admissions and among patients with left ventricular ejection fraction (LV-EF) <45% (1.7% versus 0.2%, p  < 0.001). At multivariable analysis, urgent admission and LV-EF <45%, but not primary diagnosis of coronary artery disease, remained independent predictors of LT-VA. At the time of the event, 97.1% fulfilled either class I or class II indications for telemetry monitoring according to the American Heart Association guidelines. Survival to discharge with good neurological status was 70.6%. Conclusions: acutely ill patients with heart failure and LV systolic dysfunction showed the highest rate of LT-VAs, regardless of the underlying cardiac disease (ischemic or non-ischemic). Current guidelines demonstrated high sensitivity in identifying patients at risk. These findings may favor proper utilization of telemetry monitoring resources.